Burden of dilated perivascular spaces in patients with moyamoya disease and moyamoya syndrome is related to middle cerebral artery stenosis - Han, Guangsong; Fan, Xiaoyuan; Hong, Yuehui; Zhou, Lixin; Zhu, Yicheng; Feng, Feng; Yao, Ming; Ni, Jun (Frontiers in Neurology, 2023)
Background and Objective: The correlation between intracranial large artery disease and cerebral small vessel disease (CSVD) has become a noteworthy issue. Dilated perivascular space (dPVS) is an important marker of CVSD, one of whose pathological mechanisms has been considered to be cerebral atrophy. DPVS was found to be associated with vascular stenosis in patients with moyamoya disease (MMD), but the underlying mechanism remains unclear. The purpose of our study is to explore the correlation between middle cerebral artery (MCA) stenosis and central semiovale dilated perivascular space (CSO-dPVS) in patients with MMD/moyamoya syndrome (MMS) and whether brain atrophy plays a mediating role. Methods: A total of 177 patients were enrolled in the single-center MMD/MMS cohort. All 354 cerebral hemispheres were divided into three groups according to dPVS burden: mild (dPVS 0-10), moderate (dPVS 11-20), and severe (dPVS >20). The correlations between cerebral hemisphere volume, MCA stenosis and CSO-dPVS were analyzed, and the confounding factors were age, gender and hypertension. Results: After adjustment of age, gender and hypertension, degree of MCA stenosis was independently and positively associated with ipsilateral CSO-dPVS burden (standardized coefficients β=0.247, P＜0.001). Stratified analysis found that subgroup with severe CSO-dPVS burden presented a significantly higher risk of having severe stenosis of MCA (p＜0.001, OR=6.258, 95%CI [2.347, 16.685]). Of note, no significant correlation between CSO-dPVS and ipsilateral hemisphere volume was found (p=0.055). Conclusions: In our MMD/MMS cohort, there is a clear correlation between the MCA stenosis and CSO-dPVS burden, which may be direct effect of large vessel stenosis without brain atrophy as a mediator.